Negotiating a Text Mining License for Faculty Researchers. - Williams, Leslie A.; Fox, Lynne M.; Roeder, Christophe; Hunter, Lawrence (Information Technology & Libraries, 2014)
This case study examines strategies used to leverage the library's existing journal licenses to obtain a large collection of full-text journal articles in XML format, the right to text mine the collection, and the right to use the collection and the data mined from it for grant-funded research to develop biomedical natural language processing (BNLP) tools. Researchers attempted to obtain content directly from PubMed Central (PMC). This attempt failed because of limits on use of content in PMC. Next, researchers and their library liaison attempted to obtain content from contacts in the technical divisions of the publishing industry. This resulted in an incomplete research data set. Researchers, the library liaison, and the acquisitions librarian then collaborated with the sales and technical staff of a major science, technology, engineering, and medical (STEM) publisher to successfully create a method for obtaining XML content as an extension of the library's typical acquisition process for electronic resources. Our experience led us to realize that text-mining rights of full-text articles in XML format should routinely be included in the negotiation of the library's licenses.